@siriusmartM to Daily Maths Challenges • 9 months ago[2024/05/18] Not a telescoping seriesimagemessage-square3arrow-up131arrow-down10file-text
arrow-up131arrow-down1image[2024/05/18] Not a telescoping series@siriusmartM to Daily Maths Challenges • 9 months agomessage-square3file-text
minus-squaremathemachristian[he]linkfedilink2•edit-27 months ago solution Assuming the series converges it converges absolutely. Therefore sumn/2(n-1) n >= 1 = sum(n+1)/2n n >= 0 = sumn/2n n >= 0 + sum1/2n n >= 0 = sumn/2n n >= 0 + 2 = sumn/2n n >= 1 + 2 => sumn/2(n-1) n >= 1 = sumn/2n n >= 1 + 2 => 2 = sumn/2(n-1) n >= 1 - sumn/2n n >= 1 = sumn/2(n-1) - n/2n n >= 1 = sumn/2n n >= 1 = 1/2 * sumn/2(n-1) n >= 1 => sumn/2(n-1) n >= 1 = 4
solution
Assuming the series converges it converges absolutely. Therefore
sumn/2(n-1)
= sum(n+1)/2n
= sumn/2n + sum1/2n
= sumn/2n + 2
= sumn/2n + 2
=>
sumn/2(n-1) = sumn/2n + 2
=>
2 = sumn/2(n-1) - sumn/2n
= sumn/2(n-1) - n/2n
= sumn/2n
= 1/2 * sumn/2(n-1)
=>
sumn/2(n-1) = 4